2000
DOI: 10.4049/jimmunol.165.3.1438
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cell Surface Receptors in the Activation of Human B Cells by Phosphorothioate Oligonucleotides

Abstract: Phosphorothioate oligodeoxynucleotides (sODN) containing the CpG motif or TCG repeats induce T cell-independent polyclonal activation of human B cells. To elucidate the mechanism of this response, the role of cell surface receptors was investigated. Sepharose beads coated with stimulatory but not nonstimulatory sODNs induced B cell proliferation comparably with soluble sODNs. The B cell stimulatory activity of Sepharose-bound sODN did not result from free sODN released from the beads since media incubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…strictly dependent on the CpG motif and costimulation of the non-CpG-ODN pZ2 with IL-2 or CD40 ligand results in a moderate and delayed stimulation 21,24 with upregulation of cyclin D2 and cyclin D3 at later time-points (Figure 3a). Stimulation by oligonucleotides lacking a CpG motif might be attributed to an unspecific effect mediated by the phosphothioate backbone, 25 unspecific effects of non-CpG-ODN at higher concentrations 29 or other stimulatory oligonucleotide sequences. 30 The cdk inhibitor p27 is of pivotal importance in regulating progression through the cell cycle in lymphocytes 13,31 and either reduced or increased expression is involved in the pathophysiology of lymphoproliferative disorders.…”
Section: Figurementioning
confidence: 99%
“…strictly dependent on the CpG motif and costimulation of the non-CpG-ODN pZ2 with IL-2 or CD40 ligand results in a moderate and delayed stimulation 21,24 with upregulation of cyclin D2 and cyclin D3 at later time-points (Figure 3a). Stimulation by oligonucleotides lacking a CpG motif might be attributed to an unspecific effect mediated by the phosphothioate backbone, 25 unspecific effects of non-CpG-ODN at higher concentrations 29 or other stimulatory oligonucleotide sequences. 30 The cdk inhibitor p27 is of pivotal importance in regulating progression through the cell cycle in lymphocytes 13,31 and either reduced or increased expression is involved in the pathophysiology of lymphoproliferative disorders.…”
Section: Figurementioning
confidence: 99%
“…Recent work has shown that the effects of the unmethylated CpG dinucleotides are mediated via a Toll-like receptor, TLR9. 43 Although there is some debate about the requirement for internalisation to obtain CpG stimulation of immune cells, [44][45][46][47] the immunostimulatory effect can be blocked by chloroquine and related compounds suggesting a role for endocytosis in the CpG-driven activation of the immune system. 45,48 The electrotransfer of plasmid probably avoids the endosomal pathway by directly introducing the plasmid into the cytoplasm of the cell and thus reducing the pool of unmethylated CpG dinucleotides available for stimulation of the TLR9.…”
Section: Figure 4 Total Level Of Expression Of ␤-Galactosidase In Musmentioning
confidence: 99%
“…CpG and nonCpG share common surface receptors and bind to them with the same affinity (5). However, binding of nonCpG failed to induce the maturation or activation of APCs (17).…”
mentioning
confidence: 99%
“…ODNs containing CpG motifs (CpG) induce the expression of costimulatory molecules and IL-12 in APCs, which are in turn capable of inducing Th1 cells (1)(2)(3)(4). These steps are initiated by the binding of CpG to APCs, and appear to be mediated by surface receptors specific for ODNs (5). Although ODNs bind to several surface molecules (6 -13), the identities of the receptors involved in the CpG-mediated activation have not been determined yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation